Advocacy and Legal Aid During Covid-19 Pandemic: How Indonesia Survives? - Galuh Dwi Novanda (The Indonesian Journal of International Clinical Legal Education, 2020)
The spread of the corona virus or better known as covid-19 in Indonesia is a serious matter that needs to be dealt with immediately considering the number of victims caused by the virus that was first discovered in Wuhan. As in mid-March, after the first death in Indonesia due to the corona virus and the designation of the catastrophic virus as a global pandemic by WHO or the World Health Organization, this indicates that the government must be tougher in controlling corona virus transmission in Indonesia. Even since March 15, 2020 Indonesia has determined the status of the co-19 distribution as a national disaster. The implications of the outbreak of the pandemic are the impact on problems both in the health and economic fields. In connection with health issues, the Indonesian government itself has established a public health emergency as stated in the Decree of the Head of the National Disaster Management Agency. This is as stated in Article 10 of Law Number 6 Year 2018 on Health Outrageousness as seems to be a lockdown consideration, there are large-scale social restrictions which are clearly evident in article 59 paragraph (2) which includes the consolation of schools and workplaces, restrictions on religious activities and / or restrictions on activities at public places or facilities.